Research Progress on Intervention Measures for Fall Prevention among the Elderly - Sharon R Lewis; Lisa McGarrigle; Ewa Klimek Piskorz (Journal of Public Health and Preventive Medicine, 2026)
Falls represent one of the most significant public health challenges facing the aging global population, contributing substantially to morbidity, mortality, and healthcare costs. This review synthesizes recent research progress on intervention measures for fall prevention among older adults, encompassing exercise-based interventions, multifactorial approaches, medication management and deprescribing, digital health technologies, nutritional supplementation, cognitive-behavioral strategies, and environmental modifications. Evidence from systematic reviews and meta-analyses published between 2019 and 2026 demonstrates that exercise interventions, particularly those incorporating balance and strength training, remain the most robustly supported strategy for reducing fall rates. Multifactorial interventions show consistent benefits, especially when actively implemented with exercise and environmental modification components. Emerging digital health technologies offer promising tools for fall detection and prediction, though their clinical effectiveness requires further validation. Medication review and deprescribing of fall-risk-increasing drugs (FRIDs) represent a critical yet underutilized intervention. Vitamin D supplementation at 800–1000 IU/day demonstrates efficacy in fall prevention, particularly among vitamin D-deficient individuals, though the evidence regarding high-dose supplementation remains controversial. Despite the accumulating evidence base, significant implementation gaps persist, highlighting the need for integrated, person-centered approaches that address both intrinsic and extrinsic risk factors. Future research should focus on optimizing intervention delivery, enhancing implementation fidelity, and developing hybrid models that combine technological innovation with evidence-based clinical strategies.